Reconstruction of Post-pandemic Early Childhood Religious Attitudes Against the Effects of Excessive Gadget Use Through Sigmund Freud's Psycho-Analysis Approach - Novita Nur Hamidah; Ratih Arruum Listiyandini (Institut Agama Islam Negeri Madura, 2022)
Over the past year, the pandemic has had a major impact on the use of gadgets, one of which is at an early age in Indonesia. The latest data obtained from the Central Statistics Agency in December 2020 showed that around 3.5% of children under five and 47.7% of preschoolers had used gadgets in their daily lives during the pandemic. Surely this can interfere with the development of early childhood, especially in the development of religious attitudes. This research is to obtain information about excessive gadget use in early childhood during the pandemic, as well as to obtain solutions and efforts to reconstruct early childhood religious attitudes towards the effects of excessive gadget use after analysis through the Freudian approach. The object of this research is early childhood (1-6 years) and their parents. The method used in this research is descriptive qualitative research method, which was obtained from the study of literature. The results showed that the use of gadgets in early childhood during the pandemic was the lack of intensive supervision by each parent and also boredom during the pandemic. Solutions and efforts to reconstruct religious attitudes of early childhood to the effects of excessive use of gadgets post-pandemic can be done through Sigmund Freud's psycho-analysis approach by intensive parenting and games.